1996
DOI: 10.1021/bi961805f
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Barrier Hydrogen Bond in Subtilisin:  1H and 15N NMR Studies with Peptidyl Trifluoromethyl Ketones

Abstract: The N delta 1 proton of His 64 forms a hydrogen bond with Asp 32, as part of the catalytic triad in serine proteases of the subtilisin family. His 64 in subtilisin has been studied by 1H and 15N NMR spectroscopy in the presence and absence of peptidyl trifluoromethyl ketones (TFMKs) that are transition state analog inhibitors. For subtilisin Carlsberg, the downfield resonance of the imidazolium N delta 1 proton is approximately 18.3 ppm and the D/H fractionation factor is 0.55 +/- 0.04 at pH 5.5 (11 degrees C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 55 publications
8
104
1
Order By: Relevance
“…The 15 N chemical shift was determined to be 180 Ϯ 10 ppm by a series of continuous wave decoupling experiments (spectra not shown). This 15 N chemical shift value is close to the typical value for a ϭ NH ϩ in model compounds (ϳ175 ppm) (10,11), suggesting that His 32 is largely positively charged. The protonation state of His 32 at pH 5.0 is consistent with its pK a value described in the next section.…”
Section: Resultssupporting
confidence: 72%
“…The 15 N chemical shift was determined to be 180 Ϯ 10 ppm by a series of continuous wave decoupling experiments (spectra not shown). This 15 N chemical shift value is close to the typical value for a ϭ NH ϩ in model compounds (ϳ175 ppm) (10,11), suggesting that His 32 is largely positively charged. The protonation state of His 32 at pH 5.0 is consistent with its pK a value described in the next section.…”
Section: Resultssupporting
confidence: 72%
“…The absence of a signal at ~ 15 p.p.m. due to the N δ 1 proton of imidazole [30] and the presence of the signals at ~13 and ~19 p.p.m. due to the N δ 1 and N ε 2 protons of the imidazolium ion of histidine-64 shows that when the glyoxal inhibitor is bound to subtilisin the active site histidine residue (Histidine-64) is fully protonated and its pK a is greater than 10.5 (Fig.…”
Section: H-nmr Of the The Hydrogen Bonded Protons Of The Z-ala-ala-mentioning
confidence: 98%
“…It has been suggested that in chymotrypsin and subtilisin complexes with inhibitors the active site histidine is only partially charged (between 0.5 and 1.0) due to the depolarization of LBHB, 2,3,25 as if the bridging proton is partially (about 20 -30%) transferred from the donor (active site His) to the acceptor (active site Asp). However, the only experimental evidence presented is the Here we present a more comprehensive analysis of both imidazole NH chemical shifts in comparisons with those in free enzyme as well as in model compounds, which strongly supports a partially positively charged H48 in the sPLA 2 -HK32 complex.…”
Section: -Hk32 Complexmentioning
confidence: 99%